If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2(-6 + 3) = 0 Combine like terms: -6 + 3 = -3 3 + -2(-3) = 0 Multiply -2 * -3 3 + 6 = 0 Combine like terms: 3 + 6 = 9 9 = 0 Solving 9 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| log(8)(x-12)+log(8)x=2 | | 5x=-19 | | 4x*x=100 | | 29=6*175+b | | 17=6*75+b | | -16x^2+96x=0 | | t-(-16)=9 | | -8-(-10)= | | 0.7(4x+8)=1.7-(x+2) | | y+0.2=0.6y+1.8 | | 23=6*125+b | | 56=2x-9x | | 8x^2-x+6=0 | | 84=9x+7 | | ln(3x)+ln(2x)=9 | | 2(x-1)+3(2x+1)=-7 | | 84=9x+10 | | -4-(-6)= | | x-7=6x-3 | | 12x^2=28 | | 3g+3=5(3*g) | | -46k-19(k-8)-(4-2k)= | | -46k-19(l-8)-(4-2k)= | | 3.5x+6=12.5 | | x-9=-6x-3 | | -19(3p-115)-425+234p= | | 7(u-8)=(3u+4) | | 1+3x=x | | 90=10x+75 | | 696969= | | y+6(8-2y)-3(7+x)+9= | | p^2+3p-4=0 |